Effects of external protons on single cardiac sodium channels from guinea pig ventricular myocytes (The Rockefeller University Press, 1991)
The effects of external protons on single sodium channel currents recorded from cell-attached patches on guinea pig ventricular myocytes were investigated. Extracellular protons reduce single channel current amplitude in a dose-dependent manner, consistent with a simple rapid channel block model where protons bind to a site within the channel with an apparent pKH of 5.10. The reduction in single channel current amplitude by protons is voltage independent between -70 and -20 mV. Increasing external proton concentration also shifts channel gating parameters to more positive voltages, consistent with previous macroscopic results. Similar voltage shifts are seen in the steady- state inactivation (h infinity) curve, the time constant for macroscopic current inactivation (tau h), and the first latency function describing channel activation. As pHo decreases from 7.4 to 5.5 the midpoint of the h infinity curve shifts from -107.6 +/- 2.6 mV (mean +/- SD, n = 16) to -94.3 +/- 1.9 mV (n = 3, P less than 0.001). These effects on channel gating are consistent with a reduction in negative surface potential due to titration of negative external surface charge. The Gouy-Chapman-Stern surface charge model incorporating specific proton binding provides an excellent fit to the dose-response curve for the shift in the midpoint of the h infinity curve with protons, yielding an estimate for total negative surface charge density of -1e/490 A2 and a pKH for proton binding of 5.16. By reducing external surface Na+ concentration, titration of negative surface charge can also quantitatively account for the reduction in single Na+ channel current amplitude, although we cannot rule out a potential role for channel block. Thus, titration by protons of a single class of negatively charged sites may account for effects on both single channel current amplitude and gating.